Confirmation of mutation and genetic stability of the M4 generation of chili pepper’s (Capsicum frutescens L.) Ethyl Methane Sulfonate (EMS) mutant based on morphological, physiological and molecular characters - ESTRI LARAS ARUMINGTYAS; ATIATURROCHMAH ATIATURROCHMAH; JONI KUSNADI (Society for Indonesian Biodiversity, 2023)
Abstract. Arumingtyas EL, Atiaturrochmah, Kusnadi J. 2023. Confirmation of mutation and genetic stability of the M4 generation of chili pepper’s (Capsicum frutescens L.) Ethyl Methane Sulfonate (EMS) mutant based on morphological, physiological and molecular characters. Biodiversitas 24: 531-538. The initial generation of Ethyl Methane Sulfonate (EMS) random mutations usually still shows high variation due to allele segregation. This research aimed to confirm the genetic differences between the M4 generation of chili pepper (Capsicum frutescens L.) mutant resulted from EMS mutations (G7/01) and the initial line (G7), and the stability of the mutant based on morphological, physiological, and molecular characters. The morphological characters and the capsaicinoid content of the mutants G7/01 with the initial line (G7) were compared. The capsaicinoid content and fruit spiciness were measured by spectrophotometer ? 280 nm. Molecular characterization was conducted using Random Amplified Polymorphic DNA (RAPD) genetic markers. Based on the morphological characters, the G7/01 mutants have some superior properties compared to the initial line G7. All the G7/01 mutant plants contain higher capsaicinoid compounds than the initial line plants. The dendrogram developed based on RAPD profile showed that all the mutant plants were positioned apart from the initial line plant, suggesting that there are some genomic changes in the mutants compared to the initial line plants. All the mutant plants, except T1, showed insignificant variation in morphological characteristic, capsaicin content, and RAPD profile, indicating genetic stability.